Hydrogen Reduction Behavior and Microstructure Characteristics of WO3-NiO-CuO Powder Mixture - Youn Ji Heo; Eui Seon Lee; Ji Young Kim; Sung-Tag Oh; Jongmin Byun (Archives of Metallurgy and Materials)
The characteristics and hydrogen reduction behavior of W-0.8 wt% Ni-0.4 wt% Cu powder synthesized from WO3-NiOCuO composite powder have been investigated. The metal oxide powder mixtures were prepared using a ball milling process. XRD analysis and HR-TEM revealed that the oxide powders are changed to W and CuNi alloy powders with an average particle size of about 100 nm by hydrogen reduction. To understand the reduction behavior of oxide powders, TG analysis was performed, and the reduction kinetics was evaluated by the amount of peak shift with heating rates. The activation energies for the reduction of WO3-NiO-CuO, estimated by the slope of the Kissinger plot, were measured as 60.6-114.4 kJ/mol depending on reduction steps.